HDAC10 upregulation contributes to interleukin 1β‐mediated inflammatory activation of synovium‐derived mesenchymal stem cells in temporomandibular joint. Issue 8 (4th December 2018) - Liao, Wenting; Sun, Jiadong; Liu, Wenjing; Li, Wenyu; Jia, Jiaxin; Ou, Farong; Su, Kai; Zheng, Youhua; Zhang, Zhiguang; Sun, Yangpeng
Abstract: Histone deacetylases (HDACs) are important in chronic inflammation, and inflammatory responses affect synovium‐derived mesenchymal stem cell (SMSC) function in temporomandibular joint repair. However, the effect of HDACs on SMSC inflammatory activation remains unclear. In this study, temporomandibular joint fibroblast‐like synoviocytes obtained from osteoarthritis patients met the minimal mesenchymal stem cell criteria. Interleukin 1β (IL‐1β) upregulated IL‐6 and IL‐8 expression in SMSCs through nuclear factor‐κB (NF‐κB) pathway activation. IL‐6 and IL‐8 upregulation were blocked by broad‐acting HDAC inhibitors SAHA and LBH589. MC1568 alleviated IL‐1β activation of SMSCs, whereas CI994 and FK228 produced a minimal or opposite effect in vitro. We also found HDAC10 was highly associated with localized IL‐1β expression in vivo and in vitro. HDAC10 knockdown alleviated IL‐1β‐mediated SMSC activation and blocked NF‐κB pathway activation. Conversely, HDAC10 overexpression promoted IL‐6 and IL‐8 expression and IL‐1β‐mediated NF‐κB pathway activation. In conclusion, HDAC10 upregulation contributed to IL‐1β‐mediated inflammatory activation of SMSCs, indicating that HDAC10 may be a novel therapeutic target. Abstract : The inflammation activation of synovium‐derived mesenchymal stem cells (SMSCs) mediated by interleukin 1β (IL‐1β) could be blocked by the histone deacetylase (HDAC) inhibitors, vorinostat, and panobinostat, by inhibiting nuclear factor‐κB (NF‐κB) pathway activation. HDAC10 upregulation contributed to inflammatory activation by IL‐1β through the NF‐κB pathway in SMSCs, indicating that it might be a new therapeutic target of temporomandibular joint disorders.